A novel exponential‐type anti‐windup method applied to the power converter in marine electrical propeller system. Issue 7 (8th February 2022) - Gao, Bo; Wang, Guoling; Li, Zhenyu; Song, Wujian; Lin, Honggui
Abstract: This paper proposes a novel exponential anti‐windup method for a high‐proportional‐load marine electrical propeller system, allowing the system to respond to changes in working conditions that would make the control system operate in the open‐loop state and severely affect the system stability and dynamic response speed. First, the commonly used inverse calculation type and conditional integration type anti‐windup methods are discussed, and the two methods are compared and analysed. The proposed exponential anti‐integral saturation method is obtained by introducing an exponential link in the PI controller to weaken the effect of the integral link when the controller output is saturated to improve the control performance of the traditional anti‐integral saturation method when the operating conditions of the marine electrical propeller system change. To verify the accuracy of the theoretical analysis, experiments were conducted using starsim. The experimental results verify that the theoretical analysis and parameter design are correct and superior and have the characteristics of fast desaturation and small overshoot of the system. The method has good theoretical research significance and practical application prospects for improving the comprehensive performance of marine electrical propeller systems.